âASMARALOKA BESTARIâ MUSEUM GEOPARK KALDERA TOBA - Tsara Nabilah, Edly
This final project that will be carried out is the Toba Caldera Geopark Museum. The project is located in Ajibata District, Toba Samosir Regency, North Sumatra. This location was chosen because the Toba Caldera is one of the Global Geopark Network UNESCO (GGN) candidates and also included in 10 National Strategic Tourism Areas (KSPN). The project’s design aims to create an education-based tourism area that is friendly and accessible to all groups and empowers local communities. Hopefully this museum can actualize the integration between tourism, culture, a place for providing data, and education about the history of the formation of the Toba Caldera to the public and tourists. In addition, this museum will be a catalyst for the development of economic, social and cultural aspects around the Toba Caldera.